Portrait of Pastoral Care of Factory Employees in the Industrial Area of the Church of Saint Stanislaus, Girisonta Parish - Christina Putri Indah Nugraheni; Anselmus Joko Prayitno; Nerita Setiyaningtyas (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2025)
The Parish of Saint Stanislaus Girisonta, situated in Semarang Regency, is surrounded by numerous industrial factories, attracting a significant number of Catholic migrant workers. However, the Church lacks comprehensive data on these migrants and has not yet developed a dedicated pastoral program to address their spiritual needs. This study examines the current state of pastoral care for factory employees in Girisonta Parish, explores their expectations for spiritual support, and evaluates the implementation of relevant pastoral initiatives. Using a qualitative research approach, data were collected through observation, interviews, and documentation. The findings reveal that while pastoral care in Girisonta Parish is generally well-structured, it has not been specifically adapted to the needs of factory workers and migrants. Employees express the need for more flexible pastoral services, including the formation of a Catholic employee community, Masses outside regular working hours, and spiritual guidance that accommodates their work schedules. Despite the increasing presence of Catholic factory workers, no structured pastoral program currently exists to provide consistent support for them. This study highlights the urgency of establishing targeted pastoral initiatives to foster a stronger spiritual connection among Catholic migrant workers in Girisonta Parish.